## Explanation

To find the value of the expression when $n = 3$, we'll first simplify the given expression:

$-2n (5 + n - 8 - 3n)$### Simplify the expression inside the parentheses

Combine like terms inside the parentheses:

$5 + n - 8 - 3n = 5 - 8 + n - 3n = -3 - 2n$Now, we substitute this back into the original expression:

$-2n \cdot (-3 - 2n)$### Substitute $n = 3$

Next, we substitute $n = 3$ into the simplified expression:

$-2(3) \cdot (-3 - 2(3))$This becomes:

$-6 \cdot (-3 - 6)$Further simplifying inside the parentheses:

$-6 \cdot (-9)$### Final Calculation

Calculate the product:

$-6 \cdot (-9) = 54$Therefore, the **value** of the expression when $n = 3$ is: